Factors Influencing Young Consumers’ Impulse Intentions Toward Visiting Pop-Up Stores in South Africa - Miriam-Miri Retief; Bertha Jacobs; Ann-Marie Fiore (Journal of Marketing and Consumer Behaviour in Emerging Markets)
Consumers are constantly seeking out new and memorable experiences. This study empirically examines how external factors, such as the characteristics of innovation (relative advantage, trialability, observability, low complexity, compatibility) and exterior store design, and internal factors (positive mood, hedonic motivations, consumer innovativeness) aff ect young consumers’ impulse intention toward visiting pop-up stores in the South African context. Survey data was collected from a convenient sample of 461 students from two universities in South Africa via a self-administered questionnaire. Multiple regression analysis revealed that (a) external factors related to the characteristics of innovation (i.e., compatibility and low complexity), (b) exterior store design, and (c) the internal factor, consumer innovativeness, had a signifi cant influence on consumers’ impulse intentions to visit pop-up shops. The study examined pop-up retail through the lens of impulse behaviour in an emerging market. The study contributes to the understanding of factors influencing the success of pop-up stores in emerging markets. In particular, the understanding of the factors that lead to impulse intentions towards pop-up retail, which has been overlooked in research.